Nucleus-cytoskeleton communication impacts on OCT4-chromatin interactions in embryonic stem cells - Romero, Juan José (2021)
Background: The cytoskeleton is a key component of the system responsible for transmitting mechanical cues from the cellular environment to the nucleus, where they trigger downstream responses. This communication is particularly relevant in embryonic stem (ES) cells since forces can regulate cell fate and guide developmental processes. However, little is known regarding cytoskeleton organization in ES cells, and thus, relevant aspects of nuclear-cytoskeletal interactions remain elusive. Results: We explored the three-dimensional distribution of the cytoskeleton in live ES cells and show that these filaments affect the shape of the nucleus. Next, we evaluated if cytoskeletal components indirectly modulate the binding of the pluripotency transcription factor OCT4 to chromatin targets. We show that actin depolymerization triggers OCT4 binding to chromatin sites whereas vimentin disruption produces the opposite effect. In contrast to actin, vimentin contributes to the preservation of OCT4-chromatin interactions and, consequently, may have a pro-stemness role. Conclusions: Our results suggest roles of components of the cytoskeleton in shaping the nucleus of ES cells, influencing the interactions of the transcription factor OCT4 with the chromatin and potentially affecting pluripotency and cell fate.